The Divergence in Bacterial Components Associated with Bactrocera dorsalis across Developmental Stages - Zhao, Xiaofeng; Zhang, Xiaoyu; Chen, Zhenshi; Wang, Zhen; Lu, Yongyue; Cheng, Daifeng (Frontiers in Microbiology, 2018)
Eco-evolutionary dynamics of microbiotas at the macroscale level are largely driven by ecological variables. The diet and living environment of the oriental fruit fly, Bactrocera dorsalis, diversify during development, providing a natural system to explore convergence, divergence and repeatability in patterns of microbiota dynamics as a function of the host diet, phylogeny and environment. Here, we characterized the microbiotas of 47 Bactrocera dorsalis individuals from three distinct populations by 16S rRNA amplicon sequencing. A significant deviation was found within the larvae, pupae and adults of each population. Pupae were characterized by an increased bacterial taxonomic and functional diversity. Principal components analysis showed that the microbiotas of larvae, pupae and adults clearly separated into three clusters. Acetobacteraceae, Lactobacillaceae and Enterobacteriaceae were the predominant families in larval and adult samples, and PICRUSt analysis indicated that phosphoglycerate mutases and transketolases were significantly enriched in larvae, while phosphoglycerate mutases, transketolases and proteases were significantly enriched in adults, which may support the digestive function of the microbiotas in larvae and adults. The abundances of Intrasporangiaceae, Dermabacteraceae (mainly Brachybacterium) and Brevibacteriaceae (mainly Brevibacterium) were significantly higher in pupae, and the antibiotic transport system ATP-binding protein and antibiotic transport system permease protein pathways were significantly enriched there as well, indicating the defensive function of microbiotas in pupae. Overall, differences in the microbiotas of the larvae, pupae and adults are likely to contribute to differences in nutrient assimilation and living environments.